The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7774/cevr.2018.7.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak investigation of pertussis in an elementary school: a case-control study among vaccinated students

Abstract: PurposeA pertussis patient from an elementary school, in Gyeonggi Province, Korea, was notified to public health authority on July 25, 2017. Epidemiologic investigation was conducted to identify the magnitude, possible source of infection and risk factors for this outbreak on August 17, 2017.Materials and MethodsA case was defined as the school student experiencing cough for more than two weeks with or without paroxysmal, whoop, or post-tussive vomiting. Control was defined as the student polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…There were five studies about burden in Japan [57][58][59][60][61], four in South Korea [28,[62][63][64], one in India [29], and one which included three Asian countries (Taiwan, Malaysia, and Thailand) [55].…”
Section: Search Resultsmentioning
confidence: 99%
“…There were five studies about burden in Japan [57][58][59][60][61], four in South Korea [28,[62][63][64], one in India [29], and one which included three Asian countries (Taiwan, Malaysia, and Thailand) [55].…”
Section: Search Resultsmentioning
confidence: 99%
“…In 2003, the Korea Center for Disease Control and Prevention reported that the rate of tetanus and diphtheria/tetanus, diphtheria, and acellular pertussis (Td/Tdap) vaccination among adults aged 19 years and over was only 7.3%. 21 The pertussis vaccination for adult is very important considering that there have been large outbreaks in the United States and Europe, 22 pertussis epidemic have occurred frequently in Korea, 23 24 and adult role as important mediators. 25 HCWs have a high likelihood of contact with pertussis patients and there are many immunocompromised patients and infants who are high-risk group of pertussis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentations associated with B. pertussis were reported in 9 studies included in this review, 21,25,26,29,31,[33][34][35][36] of which the majority were conducted in adolescents and adults. 25,26,29,[33][34][35] Regardless of age, the most common presentations of pertussis were paroxysmal cough followed by whooping cough, post-tussive vomiting and fever.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The vaccination status of confirmed or suspected pertussis cases was reported in 8 studies. 21,23,27,29,31,33,36,37 A total of five studies that focused on the pediatric population reported that the majority of the subjects delayed vaccination or were not vaccinated according to the recommended schedules. 21 The total number of studies depicted in the figure is 24 as five studies reported information for more than one group.…”
Section: Impact Of Vaccination and Pertussis Disease Burdenmentioning
confidence: 99%
See 1 more Smart Citation